Global Sentiments Surrounding the COVID-19 Pandemic on Twitter: Analysis of Twitter Trends - Lwin, May Oo; Lu, Jiahui; Sheldenkar, Anita; Schulz, Peter Johannes; Shin, Wonsun; Gupta, Raj; Yang, Yinping (JMIR Publications, 2020)
BackgroundWith the World Health Organization's pandemic declaration and government-initiated actions against coronavirus disease (COVID-19), sentiments surrounding COVID-19 have evolved rapidly. ObjectiveThis study aimed to examine worldwide trends of four emotions-fear, anger, sadness, and joy-and the narratives underlying those emotions during the COVID-19 pandemic. MethodsOver 20 million social media twitter posts made during the early phases of the COVID-19 outbreak from January 28 to April 9, 2020, were collected using "wuhan," "corona," "nCov," and "covid" as search keywords. ResultsPublic emotions shifted strongly from fear to anger over the course of the pandemic, while sadness and joy also surfaced. Findings from word clouds suggest that fears around shortages of COVID-19 tests and medical supplies became increasingly widespread discussion points. Anger shifted from xenophobia at the beginning of the pandemic to discourse around the stay-at-home notices. Sadness was highlighted by the topics of losing friends and family members, while topics related to joy included words of gratitude and good health. ConclusionsOverall, global COVID-19 sentiments have shown rapid evolutions within just the span of a few weeks. Findings suggest that emotion-driven collective issues around shared public distress experiences of the COVID-19 pandemic are developing and include large-scale social isolation and the loss of human lives. The steady rise of societal concerns indicated by negative emotions needs to be monitored and controlled by complementing regular crisis communication with strategic public health communication that aims to balance public psychological wellbeing.